The Contribution of Village Owned Enterprise (BUMDes) on Local Revenue in Tapelan Village, Bojonegoro Regency - Pujayanti, Dwi Retno; Nugroho, Mahendra Adhi (EAJ (Economic and Accounting Journal), 2023)
This study aims to analyze the financial condition of Maju Makmur Village-Owned Enterprises (BUMDes) in Tapelan Village, Bojonegoro Regency, as well as their impact on Local Original Income (PAD) in the village in 2022. A narrative approach was used in this study by collecting data through interviews with BUMDes management and related stakeholders, as well as analysis of BUMDes financial statement documents for the last three years. The results showed some significant findings. First, constraints in the form of limited capital affect the ability of Maju Makmur BUMDes to develop its business and achieve sustainable growth. Second, suboptimal managerial skills among BUMDes managers affect operational effectiveness and overall business management. Third, more access to the market is needed to expand product reach and increase the marketing of BUMDes.